EDUKASI PERAN PEMERIKSAAN RADIOGRAFI THORAKS SEBAGAI UPAYA SKRINING KESEHATAN MASYARAKAT DESA BANTERAN - Susanto, Fani; Basuki, Samudra Prihatin Hendra; Badharudin, Abid Yanuar; Nadi, Danu Tirta; Ammar, Hanif Dwi; Muaziz, Agil Abdul (FIP UNIRA MALANG, 2025)
Five major lung diseases are the leading causes of morbidity and mortality worldwide, lung and respiratory diseases are a serious global health problem. Global public health targets should prioritize lung health through health screening, which is an essential component in building a healthy society. Chest radiography is a medical screening procedure and assists in clinical diagnosis. The dominant community in Banteran Village, in particular, includes active smokers, mostly men and also have little understanding of the importance of health screening. The purpose of this activity is to educate about the importance of chest radiography in health screening procedures. The activity was carried out by assessing the level of community knowledge about health screening and the success of activities in the leadership cadres of the Muhammadiyah branch Banteran through counseling and lectures on the definition and role of chest radiography as a health screening effort. The results of this activity showed that everyone became more aware of the importance of chest radiography in health screening. With this activity, the community better understands the function of chest radiography as a health screening method and becomes more concerned about preventing disease by implementing a clean and healthy lifestyle.